2010
DOI: 10.1111/j.1744-6570.2010.01186.x
|View full text |Cite
|
Sign up to set email alerts
|

Validating Synthetic Validation: Comparing Traditional and Synthetic Validity Coefficients

Abstract: We describe a unique application of a synthetic validation technique to a selection system development project in a large organization. Job analysis data were collected from 4,725 job incumbents and 619 supervisors, and were used to identify 11 job families and 27 job components. We developed 12 tests to predict performance on these job components and conducted a concurrent validation study to collect test and job component data for 1,926 incumbents. We created a test composite for each job component and then … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 57 publications
0
9
0
Order By: Relevance
“…Van Iddekinge and Ployhart did report a few studies on maximum and typical performance; most studies have found that these performance indices are not highly correlated and that they do have different correlates (e.g., Marcus et al 2007). Johnson & Carter (2010) provided an excellent case study of the application of synthetic validity. Using job analysis data, the authors identified 11 job families and 27 job components.…”
Section: Evidence Of Test Validitymentioning
confidence: 99%
“…Van Iddekinge and Ployhart did report a few studies on maximum and typical performance; most studies have found that these performance indices are not highly correlated and that they do have different correlates (e.g., Marcus et al 2007). Johnson & Carter (2010) provided an excellent case study of the application of synthetic validity. Using job analysis data, the authors identified 11 job families and 27 job components.…”
Section: Evidence Of Test Validitymentioning
confidence: 99%
“…This vector defines how the job component performance scores should be weighted and combined to arrive at a definition of overall performance. A typical source of job component weights is mean importance ratings from the job analysis, although alternative weighting strategies such as unit weights may perform just as well (Johnson & Carter, in press).…”
Section: Description Of Synthetic Validationmentioning
confidence: 99%
“…In theory, these predictors should thus be valid predictors for any job that contains the job components identified, and the validity of tests that measure these predictors should be similar across job domains as long as they include these components. Some extant research evidence suggests that validity coefficients produced through synthetic validation are similar to coefficients produced through local validity studies (Johnson & Carter, 2010;Peterson, Wise, Arabian, & Hoffman, 2001). …”
Section: The Current Studymentioning
confidence: 99%
“…The current study bears some resemblance to "synthetic" validation approaches (e.g., Scherbaum, 2005), which involve several steps, including (generally): conducting job analyses to identify components of jobs that may be common across several jobs, measuring important predictors (often personality traits) and job performance outcomes, and choosing the most valid predictors of job components identified by job analyses (Johnson & Carter, 2010). In theory, these predictors should thus be valid predictors for any job that contains the job components identified, and the validity of tests that measure these predictors should be similar across job domains as long as they include these components.…”
Section: The Current Studymentioning
confidence: 99%